Antibody Engineering & Therapeutics 2016: The Antibody Society's annual meeting, December 11–15, 2016, San Diego, CA. Issue 8 (16th November 2016) - Larrick, James W.; Alfenito, Mark R.; Scott, Jamie K.; Parren, Paul W. H. I.; Burton, Dennis R.; Bradbury, Andrew R. M.; Lemere, Cynthia A.; Messer, Anne; Huston, James S.; Carter, Paul J.; Veldman, Trudi; Chester, Kerry A.; et al.
ABSTRACT: Antibody Engineering & Therapeutics, the largest meeting devoted to antibody science and technology and the annual meeting of The Antibody Society, will be held in San Diego, CA on December 11-15, 2016. Each of 14 sessions will include six presentations by leading industry and academic experts. In this meeting preview, the session chairs discuss the relevance of their topics to current and future antibody therapeutics development. Session topics include bispecifics and designer polyclonal antibodies; antibodies for neurodegenerative diseases; the interface between passive and active immunotherapy; antibodies for non-cancer indications; novel antibody display, selection and screening technologies; novel checkpoint modulators / immuno-oncology; engineering antibodies for T-cell therapy; novel engineering strategies to enhance antibody functions; and the biological Impact of Fc receptor engagement. The meeting will open with keynote speakers Dennis R. Burton (The Scripps Research Institute), who will review progress toward a neutralizing antibody-based HIV vaccine; Olivera J. Finn, (University of Pittsburgh School of Medicine), who will discuss prophylactic cancer vaccines as a source of therapeutic antibodies; and Paul Richardson (Dana-Farber Cancer Institute), who will provide a clinical update on daratumumab for multiple myeloma. In a featured presentation, a representative of the World Health Organization's INN expert group will provide a perspective on antibody naming. "Antibodies to watch in 2017" and progress on The Antibody Society's 2016 initiatives will be presented during the Society's special session. In addition, two pre-conference workshops covering ways to accelerate antibody drugs to the clinic and the applications of next-generation sequencing in antibody discovery and engineering will be held on Sunday December 11, 2016.